2015
DOI: 10.1160/th14-12-1031
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of Tlr9 deletion in experimental late venous thrombosis resolution and vein wall injury

Abstract: Deep vein thrombosis (DVT) resolves via a sterile inflammatory response. Defining the inflammatory response of DVT may allow for new therapies that do not involve anticoagulation. Previously, we have shown that Toll-like receptor 9 (Tlr9) gene deleted mice had impaired venous thrombosis (VT) resolution. Here, we further characterize the role of Tlr9 signaling and sterile inflammation in chronic VT and vein wall responses. First, we found a human precedent exists with Tlr9+ cells present in chronic post thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Gene knockout studies have shown a pivotal role of TLR9 in VTE resolution [22, 23]. Taken together with our findings, this suggests that TLR9 polymorphism may reduce the ability of VTE resolution and therefore may increase the risk of VTE recurrence.…”
Section: Discussionsupporting
confidence: 83%
“…Gene knockout studies have shown a pivotal role of TLR9 in VTE resolution [22, 23]. Taken together with our findings, this suggests that TLR9 polymorphism may reduce the ability of VTE resolution and therefore may increase the risk of VTE recurrence.…”
Section: Discussionsupporting
confidence: 83%
“…Further, TLR9 −/− mice had increased apoptosis, citrullinated histones, PAD4, and neutrophil elastase; and reduced TFPI ( 19 ), suggesting that TLR9 is important for normal thrombogenesis and thrombosis resolution. Lastly, M1-like (CCR2+) monocyte/macrophages were decreased in TLR9 −/− thrombi, consistent with impaired inflammatory cell influx, and this divergence was corrected with adoptive transfer of TLR9 +/+ bone marrow-derived monocytes with normalization of thrombus size ( 20 ). The new found composition of DNA-rich thrombi will likely have long-standing implications for future research in VT resolution.…”
Section: Nets In Murine Vt Modelsmentioning
confidence: 98%
“…Neutrophils, monocytes, and NETs have also been found to affect the clotting cascade in murine models of thrombosis ( 17 20 ). For example, myeloid cells roll along the venous endothelium in a P-selectin-dependent manner and produce thrombogenic tissue factor (TF) in the IVC stenosis model ( 17 ).…”
Section: Nets In Murine Vt Modelsmentioning
confidence: 99%
“…It has been shown that lack of this pattern-recognition receptor is associated with larger venous thrombi and increased levels of NETosis, necrosis, and apoptosis markers in the stasis, but not stenosis, model of DVT in mice [73] . It has also been shown that lack of TLR-9 leads to reduced monocyte recruitment to venous thrombi [81] .…”
Section: Stage 3: Blood Cell Recruitmentmentioning
confidence: 99%